2013
DOI: 10.1093/heapol/czt019
|View full text |Cite
|
Sign up to set email alerts
|

10 best resources on … mixed methods research in health systems

Abstract: Mixed methods research has become increasingly popular in health systems. Qualitative approaches are often used to explain quantitative results and help to develop interventions or survey instruments. Mixed methods research is especially important in low- and middle-income country (LMIC) settings, where understanding social, economic and cultural contexts are essential to assess health systems performance. To provide researchers and programme managers with a guide to mixed methods research in health systems, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 18 publications
(18 reference statements)
0
72
0
6
Order By: Relevance
“…Conflicted coding was resolved through dialogue between the coders to reach a consensus [27]. This qualitative interview and free response data was mixed with quantitative survey data using a convergent parallel design whereby qualitative and quantitative data are gathered concurrently and contribute equally to the interpretation and conclusions of the study [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Conflicted coding was resolved through dialogue between the coders to reach a consensus [27]. This qualitative interview and free response data was mixed with quantitative survey data using a convergent parallel design whereby qualitative and quantitative data are gathered concurrently and contribute equally to the interpretation and conclusions of the study [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Many studies emphasize on the combination of both quantitative and qualitative methods (mixed-methods) to examine professional and organizational factors in system evaluation [73,79,80]. Only two of the reviewed papers in this study used mixed methods.…”
Section: Page 14 Of 28mentioning
confidence: 99%
“…A previous study showed the potential of mixed-method studies to understand and improve health systems performance in low-and middle-income countries [79].…”
Section: Page 14 Of 28mentioning
confidence: 99%
“…This study will use convergent parallel mixed methods where an embedded qualitative study will help expose the mechanisms influencing feasibility data such as recruitment, retention, and usage [23,24]. An online randomization tool will be used to mitigate imbalance between the arms and to assess whether it is possible to recruit to both arms of the study: standard care and standard care plus TRAK.…”
Section: Methodsmentioning
confidence: 99%